Mr. putter and tabby pick the pears eaudiobook - Rylant, Cynthia (Mr. Putter & Tabby,, 2015)
Fall is Mr. Putter and Tabby's favorite time of year-a time to harvest juicy fruits and feast on baked goodies. But this year it's not going to be so easy. Old age is making Mr. Putter's legs, knees, and feet ... cranky. Even his cat Tabby suffers from a cranky tail. But that won't stop them! Mr. Putter comes up with a zingy way to pick the pears. And thanks to Mrs. Teaberry and her good dog Zeke, he and Tabby are showered with loads of yummy apple treats, but no pears—so no pear jelly. Can Mr. Putter will find a way to get pear jelly after all? This Newbery Medal honoree and her characters in the Mr. Putter Tabby series offer valuable lessons, such as the importance of never giving up, using your imagination, and trusting your friends. To the delight of listeners, John McDonough's warm voice brings these charming characters to life.